Asymmetric information and the discount on foreign-acquired degrees in Canada - Yigit Aydede; Atul A. Dar (IZA Journal of Development and Migration, 2019)
A growing wage gap between immigrant and native-born workers is well documented and is a fundamental policy issue in Canada. It is quite possible that wage differences, commonly attributed to the lower quality of foreign credentials or the deficiency in the accreditation of these credentials, merely reflect lower wage offers that immigrant workers receive due to risk aversion among local firms facing an elevated degree of asymmetric information. Using the 2006 and 2011 population censuses, this paper empirically investigates the effects of wage bargaining in labor markets on the wage gap between foreign- and Canadian-educated workers. Our results imply that a significant part of the wage gap between foreign-educated and Canadian-educated immigrant (and native-born) workers is not driven by the employers' risk aversion but by differences in human capital endowments and occupational matching quality.
Keywords: J6; J15; J61; 330; risk aversion; return to education; occupational mismatch